Cystatin C as a Predictor of Mortality and Cardiovascular Events in a Population with Chronic Kidney Disease. (11th February 2014) - Vigil, Ana; Condés, Emilia; Vigil, Luis; Gallar, Paloma; Oliet, Aniana; Ortega, Olimpia; Rodriguez, Isabel; Ortiz, Milagros; Herrero, Juan Carlos; Mon, Carmen; Cobo, Gabriela; Jimenez, Juana
Abstract : Background . We examine whether cystatin C, a surrogate marker of renal function, could identify patients with chronic kidney disease (CKD) with an increased risk of renal disease progression, death, or cardiovascular events. Methods . Data were obtained for 180 patients, with a diagnosis of chronic renal failure based on serum creatinine estimated glomerular filtration rate (eGFRcreat ) <90 mL/min/1.73 m 2 . This population was grouped in tertiles according to cystatin C and creatinine values at baseline. Cardiovascular events and overall mortality were estimated for each tertile. Predictors of overall mortality and for the development of renal disease progression were analyzed. Results . The median age was 75 years (interquartile range 69–82) and the median eGFRcreat 38 mL/min m 2 (interquartile range 33–49). Overall mortality was lower on the first and on the second tertiles of cystatin C than on the third one (HR = 0.060; 95% CI: 0.008–0.447 and HR = 0.094; 95% CI: 0.022–0.406, resp.). Deaths related to the creatinine tertiles followed the same pattern, but differences were not as large. Cardiovascular mortality was lower on the second than on the third cystatin C tertile (HR = 0.198; 95% CI: 0.040–0.987), but it did not show differences on the first and the second creatinine tertiles compared with the third one (HR = 0.126; 95% CI: 0.013–1.265 and HR = 0.403; 95% CI: 0.093–1.740). The only independent predictors of mortality during followup were baseline cystatin C (OR = 0.100; 95% CI: 0.021–0.463) and baseline uric acid (OR = 1.377; 95% CI: 1.070–1.773). Conclusion . Cystatin C may be an alternative to creatinine for detecting a high risk of death and cardiovascular events in a population with CKD.